Detection of sieric BAG3 in patients affected by cardiovascular diseases: State of art and perspectives. Issue 1 (14th December 2021) - Maffioli, Pamela; D'Angelo, Angela; Tinelli, Carmine; Falcone, Colomba; Galasso, Gennaro; Derosa, Giuseppe
Abstract: BAG3 is highly expressed in the heart and its functions are essential in maintaining cardiac muscle cells homeostasis. In the past, BAG3 was detected in serum from advanced heart failure patients and its higher levels were correlated to an increased death risk. Moreover, it has also been reported that BAG3 levels in serum are increased in patients with hypertension, a known cardiovascular risk marker. Evidence from different laboratories suggested the possibility to use BAG3‐based strategies to improve the clinical outcome of cardiovascular disease patients. This review aims to highlight the biological roles of intracellular or secreted BAG3 in myocardiocytes and propose additional new data on the levels of sieric BAG3 in patients with acute myocardial infarction (AMI), never assessed before. We evaluated BAG3 serum levels in relation to cardiovascular risk parameters in 64 AMI patients aged ≥18 years of either sex. We observed significant ( p  < .01) correlations of BAG3 positivity with dyslipidemic status and diabetic disease. We did not observe any significant correlations of BAG3 levels with smoking habit, hypertension or familiarity for AMI, although BAG3‐positive seemed to be more numerous than BAG3‐negative patients among hypertensives and among patients with familiarity for AMI. Furthermore, a significant ( p  < .001) correlation of BAG3 positivity with diuretics assumption was also noted. In conclusion, 32.8% of the patients were BAG3‐positive and were characterized by some particular features as comorbidity presence or concomitant therapies. The significance of these observations needs to be verified by more extensive studies and could help in the validation of the use of BAG3 as a biomarker in heart attack risk stratification.